The associating factors and outcomes of green supply chain management implementation â from the technological and non-technological perspectives - Sugathan, S.K. (Springer Verlag, 2015)
The ISO 140001 manufacturing firms in Malaysia are contributing towards the problems in regards to environment sustainability as result of significant amount of energy and waste being generated. ISO 14001 is essentially a certification for the best practices been adopted for environmental management. Despite being certified with environmental related accreditation, the implementation of green practices in the scope of supply chain among the firms are inadequate. With the above challenges, the study on Green Supply Chain Management (Green SCM) in relation to eco-friendly information technology solution will be investigated. The study will establish the driving factors and performance outcomes associated with the implementation of Green SCM. The significant relationships between the constructs explains the inputs which are represented with a TOE Framework. The measurement of the theoretical framework yields that Green SCM positively influences both the environmental and technological performance outcomes of the respective firms. As part of the practical implication, the study contributes towards a guideline for firms intending to adopt green practices. Â© Springer International Publishing Switzerland 2015.